ANATOMY OF THE NIGERIAN ELITE: INTERROGATING A BLIND ELITE MODEL OF THE ELITE THEORY - Okeke Remi Chukwudi (European Scientific Journal, ESJ, 2014)
The elite dimension to Nigeria’s numerous socio-economic and socio-political problems have over the years, attracted immense scholarly attention. These socio-economic and socio-political challenges have however remained oncoming. The problem of this study derives essentially from a supposition that the persistent national challenges are attrubutable to elite blindness. The study considers as novel, the blind elite model of the elite theory. Thus, the general objective of the study was to conduct an anatomy of the Nigerian elite by interrogating the blind elite model of the elite theory. The specific objectives were to (i) examine if the thesis of elite blindness, particularly in the Nigerian context was plausible and (ii) recommend how elite blindness may be dealt with, in the specific Nigerian context and also in the general context. Findings of the study indeed indicate that the elite blindness thesis is highly plausible. However, it is also classifiable as phantom and self-inflicted blindness. Findings of the study further curiously indicate that the blind Nigerian elites continue to find their ways around their elite purposes under the guidance of their less privileged compatriots. The study posits in conclusion that the self-inflicted blindness of the Nigerian elite would become history, the day their less privileged guides finally elect to go blind as well.